Eksistensi Da’i Dalam Pencegahan Stunting di Desa Mompang Jae Kabupaten Mandailing Natal - Ariadi Nasution, Zulfahmi; Hasibuan, Sahdin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2024)
The existence of Da'i in the Mompang Jae Village area has a considerable influence on stunting prevention efforts based on the results of the researchers' findings. The collaboration carried out by religious institutions with the government and health services in the Mompang Jae Village area in the process of accelerating stunting reduction is certainly inseparable from the existence of Da'i who go directly to the field to voice and preach so that people behave to implement a healthy lifestyle. This certainly requires hard work and persuasiveness and requires a special da'wah strategy in delivering da'wah about this stunting problem to the public. Stunting cases in the Mompang Jae Village area have decreased from year to year, the existence of local Da'i has a considerable impact on the process of overcoming stunting cases in Mompang Jae Village to change people's mindset or behavior to continue to live a healthy lifestyle. This is certainly in line with the habits of the people who are still very respectful, trusting and obedient to what Da'i convey through preaching about this stunting problem which is associated with the Qur'an and Hadith and the arguments that regulate this problem. Da'wah has an important role in raising public awareness about stunting. Through da'wah, it can provide teaching and direction to change the wrong path to the right one. In handling stunting, the role of da'wah has enormous potential as a solution for the community, with the aim of forming a generation based on the Qur'an and Hadith, which has strong faith, broad knowledge, good health, and mental toughness. In an effort to deal with the problem of stunting, the importance of Da'i involvement is expected to provide views from an Islamic perspective on marriage, especially related to early marriage which is the main cause of the increase in stunting cases.